Does the good life feel good? The role of positive emotion in competing conceptions of the good life - Novak, Lukas; Kiknadze, Nona (Frontiers in Psychology, 2024)
Flourishing refers to one kind of generalized well-being. Contemporary flourishing research often privileges positive emotion in the theorization and measurement of the construct, such that flourishing is frequently conceptualized as involving a predominance of positive over negative emotions. Positive emotions are thus, on some views of flourishing, seen as an essential component of 'the good life'. This paper explores the nuanced variations in conceptions of the good life, focusing on the interplay between positive emotion and flourishing. Through an analysis of contemporary perspectives on flourishing, we underscore the diversity in conceptualizations of flourishing and the implications of this diversity for flourishing theorists. Our review reveals significant disparities in perspectives regarding the significance of positive emotion in the pursuit of a good life. Furthermore, we delineate the theoretical distinctions between objective-list approaches and functional approaches to flourishing, highlighting their respective advantages and limitations. Theoretical dissensus persists regarding whether positive emotion is a necessary constituent of the good life, thus prompting a critical examination of the justification for its inclusion in flourishing models. Finally, we emphasize the need for greater theoretical clarity in defining well-being to inform both research endeavors and societal discourse. We suggest that an adequate appreciation of variation in the development and maintenance of flourishing requires admitting for more complex relationships between the construct and both positive and negative emotionality, while embracing the cultural and individual variety that are unavoidable in accurate models of human life.